Teaching business English - Ellis, Mark.; Johnson, Christine (Oxford : Oxford University Press, 1994)
This book is about: Introduction to business English; Analysing the needs of the learners; Activities and materials.
Keywords: English language; Business English; English language -- Business English -- Study and teaching